The Implementation of Curriculum Development in The Era of The Industrial Revolution 4.0 - Amirudin, Amirudin; Sugiharto, Sugiharto (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is to photograph the condition of the curriculum at the Da'wah Management Study Program, FIDKOM UIN Jakarta and then provide curriculum suggestions that can adapt to the era of the industrial revolution 4.0. Based on the results of the study, it was shown that the composition of many courses that were not balanced between University Courses (MKU) and Faculty Courses (MKF) made students too general and not focused on their expertise. There are many courses that should exist, for example entrepreneurship and practicum lecture activities that must be more and synergized with the 4.0 era. the preparation of the Da'wah Management Study Program curriculum in the form of goals/achievements, content/achievements, methods/processes and evaluation/ assessment of the curriculum development of the Da'wah Management study program is not fully in accordance with the development of the industrial revolution 4.0., Preparation of Semester Learning Plans (RPS), short syllabus and plans there are still many student assignments that have not adjusted to the conditions of the industrial revolution 4.0 so there are still many shortcomings in the preparation of the RPS.